Building business strategy at Hoa Binh Petroleum Construction Investment Joint Stock Company - PVCHB in period 2019-2023 = Xây dựng chiến lược kinh doanh ở công ty Cổ phần Đầu tư xây lắp dầu khí Hòa Bình - PVCHB trong giai đoạn 2019-2023 - Trần, Minh Vương (2020)
To formalize the theoretical issues of strategic management. Develop business strategy for PVCHB. Identify the strengths and weaknesses to provide solutions to implement the business strategy of the enterprise in the period 2019-2023